Harmonizing Civic Disposition and Local Culture: Language Politness in Classroom Management Based on TIDAR Values - NOVITASARI; MASHUD SYAHRONI; WINASTI RAHMA DIANI; FIRDA AULIA IZZATI (Universitas PGRI Kanjuruhan Malang, 2026)
Harmonizing Civic Disposition and Local Culture: Linguistic Politeness in TIDAR-Value-Based Classroom Management. Civic Education (PKn) in higher education faces a paradox between a democratic academic environment and a crisis in student communication ethics. This study offers a novel contribution by applying a micro-pragmatic perspective to civic disposition, positioning lecturers as